Indirect Taxation in Vertical Oligopoly - Martin Peitz; Markus Reisinger (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2009)
This paper analyzes the effects of specific and ad valorem taxation in an industry with downstream and upstream oligopoly. We find that in the short run, i.e. when the number of firms in both markets is exogenous, the results concerning tax incidence tend to be qualitatively similar to models where the upstream market is perfectly competitive. However, both over- and undershifting are more pronounced, potentially to a very large extent. Instead, in the long run under endogenous entry and exit overshifting of both taxes is more likely to occur and is more pronounced under upstream oligopoly. As a result of this, a tax increase is more likely to be welfare reducing. We also demonstrate that downstream and upstream taxation are equivalent in the short run while this is not true for the ad valorem tax in the long run. We show that it is normally more efficient to tax downstream.
urn:nbn:de:bvb:19-epub-13297-3
Keywords: D43; H21; H22; L13; 330; Specific Tax; Ad Valorem Tax; Value-Added Tax; Tax Incidence; Tax Efficiency; Indirect Taxation; Imperfect Competition; Vertical Oligopoly; Verbrauchsteuer; Umsatzsteuer; Lieferantenmanagement; Oligopol; Vertikale Integration; Steuerwirkung; Steuerinzidenz; Theorie